(untitled) (Pesquisa Odontológica Brasileira, 2003)
Radiotherapy is frequently employed for the treatment of head and neck squamous cell carcinoma. Among the side effects, xerostomia is one of the most important. With the objective of evaluating the role of radiotherapy in salivary flow, we performed three salivary sample collections: at the beginning of, during, and immediately after radiotherapy. The results showed that the salivary flow values of the first collection were very similar to those of the control group. However, during treatment, there was a significant decrease of the salivary flow (p = 0.0008), which continued low immediately after radiotherapy (p = 0.0009). Our study showed that radiotherapy leads to an important reduction of salivary flow during and after radiotherapy.